Drought-induced stress on rainfed and irrigated agriculture: Insights from multi-source satellite-derived ecological indicators - Chen, Yanan; Wang, Ying; Wu, Chaoyang; Rosa Ferraz Jardim, Alexandre Maniçoba da [UNESP]; Fang, Meihong; Yao, Li; Liu, Guihua; Xu, Qiuyi; Chen, Lintao; Tang, Xuguang (Elsevier, 2025)
The increasing frequency and severity of droughts, driven by rising global temperatures, are impacting crop yields. Elucidating the response of agricultural ecosystems to droughts under different management practices is vital for food security that supports the United Nations Sustainable Development Goal 2 for zero hunger. Our study revisited the spatio-temporal evolution of record-breaking drought event of 2012 in the continental United States by using a 3-month Standard Precipitation Evapotranspiration Index (SPEI3), and analyzed the impacts of such drought based on three satellite-based ecological metrics, including structural metric (LAI) and physiological metrics (GPP, GOSIF) across the irrigated and rainfed croplands, respectively. Generally, these metrics exhibited obvious seasonal dynamics, and successfully captured the drought-induced stress on agriculture in 2012. In rainfed croplands, LAI was more sensitive to drought compared to the other two metrics. Specifically, during the 2012 drought, LAI in rainfed fields was below the multi-year average at approximately day of year (DOY) 161, while GPP and GOSIF began at about DOY 177. By contrast, LAI and GPP simultaneously captured the negative anomalies in irrigated croplands at approximately DOY 169. Compared to the irrigated cropland, the rainfed cropland showed larger cumulative decreases in LAI, GPP, and GOSIF from June to September 2012 by about 3.64, 12.92 g C m−2, and 0.55 W m−2 μm−1 sr−1, respectively. Spatially, all negative anomalies increased throughout the growing season of both rainfed and irrigated croplands in the continental United States. The percentage of negative anomalies in irrigated fields was lower than in rainfed fields during this period. In this study, we illustrated that irrigation plays an important role in mitigating meteorological droughts in agroecosystems as well as providing safeguards for human food supply.
Keywords: GOSIF; GPP; Irrigated cropland; LAI; Rainfed cropland